The effects of cognitive impairment on gait in Parkinson's disease - Krupicka, Radim; Malá, Christiane; Neťuková, Slávka; Duspivová, Tereza; Vážná, Anna; Jan Novák; Růžička, Evžen; Bezdíček, Ondřej (Gait & posture, 2023)
Gait and cognitive deficits are common symptoms of Parkinson's disease (PD) [1]. Cognitive deficits can manifest themselves in gait impairment and are tested with the gait-cognitive dual task (DT) [2]. Although a study [3] showed that the cognitive deficit represented by Montreal Cognitive Assessment (MoCA) weakly correlated with DT gait parameters, the opposite question, if worse gait performance in DT correlates with cognition in patients with PD, has not been answered. Does the performance in gait-cognitive dual task correlate with the performance in MoCa test in patients with Parkinson's disease? We examined 99 de-novo, drug-naive patients with PD (59±13 years) and 58 healthy controls (CON) (60±9 years) [4]. All subjects completed an extended Timed Up & Go Test (TUG) and Montreal Cognitive Assessment (MoCA). The TUG was performed twice and captured on a 5.15m long and 0.9m wide pressure walkway (GAITRite®). Participants were instructed to walk in the two different conditions: (i) at a normal pace (ST) and (ii) at a normal pace while counting down from 100 by seven (DT). Gait velocity, cadence, and stride length were selected as representative gait parameters. Cognitive costs [(DT − ST)/ST × 100] were calculated for each parameter and the first PCA component was calculated for the threshold for gait cognitive impairment. The threshold was defined as the 10th percentile of CON and filtered patients without gate-cognitive deficit. The groupwise comparison was made using the two-sample t-test. The Pearson correlation between MoCA and gait parameters was calculated for filtered PD (31 patients, 61±13 years). The t-test revealed significant differences (p<0.05) between CON and PD in velocity cost and stride length cost. PD’s MoCA moderately correlated with the velocity cost (r=0.37) and strongly correlated with the stride length cost (r=0.52) (see Figure). Figure: Visualization of results A) Distribution and differences in gait parameters of healthy controls (CON) and patients with Parkinson's disease (PD) B) Pearson’s correlation of gait parameters and MoCA presented by r and significance (*p<0.05, **p<0.01). [Display omitted] The impairment of gait performance in PD is mainly characterized by a slower velocity with a shorter stride length and a compensatory increase in walking cadence [5]. Significant changes in velocity cost and stride length cost confirm that a cognitive task accents gait impairment. Although the studies [2,3] showed a weak correlation between MoCA and DT in patients with cognitive deficits in PD, our study showed a strong correlation in stride length for PD patients with worse DT performance. This may suggest that gait performance is dependent on cognitive performance and may be improved by cognitive training.